Abortion in the United States' bible belt: organizing for power and empowerment - Castle Mary (BMC, 2011)
Abstract Over the last 30 years, conservative power in the United States, financed and organized by Christian fundamentalist sects, the Catholic Church, and conservative corporate and political leadership, has become more threatening and potentially destabilizing of progressive democratic principles and practices. Powerful interlocking political, financial and social forces are arrayed against women in many Southern and Western states. They are having destructive effects on women's ability to control their fertility and maintain bodily integrity and health. Poor women and women of color are disproportionately affected by restrictions on abortion services. Strategically developed interventions must be initiated and managed at every level in these localities. It is urgent to coordinate and empower individuals, multiple organizations and communities to engender effective changes in attitudes, norms, behavior and policies that will enable women to obtain reproductive health services, including abortion care. This paper describes contextual factors that continue to decimate U.S. women's right to health and, then, describes a community organizing-social action project in a number of US' states aimed at reversing the erosion of women's right to have or not to have children.